2018
DOI: 10.20524/aog.2018.0317
|View full text |Cite
|
Sign up to set email alerts
|

Adapted first-line treatment of Helicobacter pylori infection in Algerian children

Abstract: BackgroundHelicobacter pylori (H. pylori) infection is acquired in early life and continues to have a high prevalence, especially in developing countries. Growing antibiotic-resistant strains necessitate adapted treatments. This study aimed to compare the efficacy, side effects, and influence of resistance of H. pylori strains between two different treatments.MethodsThis prospective, randomized blind study enrolled 112 symptomatic children infected with H. pylori (66 girls, mean age 11.1 years). Treatments, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…27 Studies demonstrated that triple therapy with PPI-AMO-CLA offers acceptable eradication rates when the strains are sensitive, and the resistance to MET does not significantly influence eradication. [32][33][34] Authors reported patients with susceptibilityguided treatment with adherence >90% of treatment achieved acceptable rates of eradication, 30 35 the rates were significantly higher in those receiving sequential therapy. 35 High doses of MET with triple therapy for 10 days in patients without culture improved eradication rates, although the desired ones were not achieved.…”
Section: Open Accessmentioning
confidence: 99%
“…27 Studies demonstrated that triple therapy with PPI-AMO-CLA offers acceptable eradication rates when the strains are sensitive, and the resistance to MET does not significantly influence eradication. [32][33][34] Authors reported patients with susceptibilityguided treatment with adherence >90% of treatment achieved acceptable rates of eradication, 30 35 the rates were significantly higher in those receiving sequential therapy. 35 High doses of MET with triple therapy for 10 days in patients without culture improved eradication rates, although the desired ones were not achieved.…”
Section: Open Accessmentioning
confidence: 99%
“…The prevalence of H pylori resistant to antibiotics differs among countries (Table ) and is usually explained by the different exposure to the corresponding antibiotics in each population . First‐line treatment should, therefore, be tailored according to the strain's susceptibility or, if tests are not available, at least according to the regional antibiotic resistance rates of H pylori strains …”
Section: Diagnosismentioning
confidence: 99%
“…Apart from high H pylori resistance to antimicrobial agents, there are other reasons for therapeutic failure, such as poor compliance, inadequate dose/duration, rapid metabolism of certain PPI, bacterial virulence factors, ineffective penetration of antibiotics into gastric mucosa, and antibiotic inactivation to low gastric pH …”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations